Advances in forensic odontology for human identification: a comprehensive review of methods, accuracy, and challenges - Riaz, Samiya (IIUM Press, 2026)
Forensic odontology provides significant possibilities for human identification in the absence of DNA and fingerprints. Dental tissues, impervious to environmental damage, offer distinctive characteristics for sex estimation, age assessment, ancestry identification, and comparative analysis. This review rigorously integrates conventional and novel methodologies. Odontometric and non-metric characteristics are extensively utilized for sex estimation and ancestry assessment; however, accuracy differs among groups, and inter-observer variability continues to exist. Age estimate methodologies, including Demirjian, Willems, Nolla, AlQahtani, Kvaal, and Cameriere, have significant dependability in children and adolescents, although their accuracy diminishes in adults owing to wider error margins. Recent advancements, such as cone-beam computed tomography, three-dimensional imaging, and artificial intelligence, demonstrate potential for automated and reproducible assessments. Nonetheless, validation studies are scarce, established methodologies are absent, and legal admissibility is ambiguous. Comparative identification remains extremely reliable with antemortem and postmortem information, while diminishing dental restorations compromise distinctiveness. Forensic odontology is essential; yet, advancement necessitates the incorporation of digital technologies, population-specific criteria, and a heightened focus on validation and ethical-legal standards.